2005
DOI: 10.1128/aem.71.7.4069-4075.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia Symbiont in the Pea Aphid Acyrthosiphon pisum : Novel Cellular Tropism, Effect on Host Fitness, and Interaction with the Essential Symbiont Buchnera

Abstract: In natural populations of the pea aphid Acyrthosiphon pisum, a facultative bacterial symbiont of the genus Rickettsia has been detected at considerable infection frequencies worldwide. We investigated the effects of the Rickettsia symbiont on the host aphid and also on the coexisting essential symbiont Buchnera. In situ hybridization revealed that the Rickettsia symbiont was specifically localized in two types of host cells specialized for endosymbiosis: secondary mycetocytes and sheath cells. Electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
250
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(268 citation statements)
references
References 46 publications
(71 reference statements)
16
250
1
1
Order By: Relevance
“…In such circumstances, symbionts monopolizing resources should be selected for at the within-host level, if this increases the efficiency of their own vertical transmission. Examples of such competitive interactions have been illustrated between secondary symbionts [6,102], but also in situations of co-infections between primary and secondary symbionts [103,104]. If symbionts evolve higher competitive ability, this may further limit the maintenance of multiple infections.…”
Section: Insects As Symbiotic Communitiesmentioning
confidence: 99%
“…In such circumstances, symbionts monopolizing resources should be selected for at the within-host level, if this increases the efficiency of their own vertical transmission. Examples of such competitive interactions have been illustrated between secondary symbionts [6,102], but also in situations of co-infections between primary and secondary symbionts [103,104]. If symbionts evolve higher competitive ability, this may further limit the maintenance of multiple infections.…”
Section: Insects As Symbiotic Communitiesmentioning
confidence: 99%
“…Arthropods are the primary host of all rickettsial species and many rickettsial species are inherited and maintained via transovarial and transstadial transmission within arthropods (Sakurai et al 2005). Vertical transmission of R. felis has been described in detail and is the primary transmission strategy in the LSU cat flea colony (Wedincamp and Foil 2002).…”
mentioning
confidence: 99%
“…Previous studies on symbiont infection density have been conducted on whole insects without symbiont cultivation: different combinations of host and symbiont genotypes were experimentally generated by microinjection, antibiotic therapy and/or introgression, and infection densities of the symbionts in the different host-symbiont combinations were evaluated by quantitative PCR. These studies have demonstrated that symbiont infection dynamics are significantly affected by the symbiont genotype (McGraw et al, 2002;Ikeda et al, 2003;Mouton et al, 2003Mouton et al, , 2004, host genotype (Kondo et al, 2005;Mouton et al, 2007), interactions between co-infecting symbionts (Koga et al, 2003;Kondo et al, 2005;Sakurai et al, 2005;Goto et al, 2006) and/or other environmental factors (Mouton et al, 2007;Anbutsu et al, 2008). However, it is not clear which symbiont genes are involved in the infection dynamics and regulation of symbiont density.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have shown that the infection density of the symbiont can affect the fidelity of vertical transmission, the degree of reproductive aberrations and the level of fitness consequences as indicated by body size, growth, survival and/or fecundity (McGraw et al, 2002;Koga et al, 2003;Mouton et al, 2004;Sakurai et al, 2005;Kikuchi et al, 2007;Kim et al, 2013b). The mechanisms underlying the infection, proliferation and maintenance of symbionts within their host organisms are therefore of ecological and evolutionary importance (Kondo et al, 2005;Engelstadter et al, 2006;Vautrin and Vavre, 2009).…”
Section: Introductionmentioning
confidence: 99%